IMPLEMENTATION OF PROFESSIONAL ZAKAT BASED ON THE REGIONAL REGULATION OF PALEMBANG CITY NUMBER 4 OF 2017 AT THE PALEMBANG CITY GOVERNMENT OFFICE - Tamudin, M.; Fitriyati, Yusida (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This paper examines the implementation of professional zakat based on the regional regulation of the city of Palembang Number 4 of 2017 concerning zakat management at the Palembang city government office.This research is a field research by conducting a study of the laws that apply in society. This study looks at the application of professional zakat based on the Regional Regulation of Palembang City Number 4 of 2017 at the Palembang City Government Office. There are 3 problem formulations in this study, including